PENGARUH COUNTRY OF ORIGIN, SOCIAL MEDIA MARKETING DAN E-WOM TERHADAP KEPUTUSAN PEMBELIAN PRODUK SOMETHINC DI JAKARTA SELATAN - Arini Pramudita (2024)
This research was conducted to determine the influence of country of origin (COO), social media marketing (SMM), and electronic word of mouth (EWOM) on purchasing decisions for Somethinc products. This study is quantitative, utilizing primary data obtained from respondents' answers through a questionnaire administered via Google Form and distributed through Line, WhatsApp, Instagram, and Telegram. The population consisted of individuals who had purchased Somethinc products, resided in South Jakarta, and were familiar with one of Somethinc's social media platforms. 100 respondents participated in the study, selected through non-probability sampling using the purposive sampling method. The research employed the Structural Equation Modeling (SEM) method with SmartPLS 4.0 as the testing tool. The study's findings revealed that the variables country of origin (COO) and electronic word of mouth (EWOM) have a positive and significant influence on purchasing decisions. In contrast, the variable social media marketing (SMM) do not have a positive and no significant influence on purchasing decisions.